Simulation of the liquid-vapor interface of molten LiBeF3 - Salanne, M; Simon, C; Turq, P; Madden, P (2007)
The structural properties of the liquid-vapor interface of an equimolar mixture of LiF and BeF2 are studied by molecular dynamics. The interaction potential include anion polarization and was constructed from first-principle calculations. The simulation result for the surface tension is in good agreement with the experimental measure. Examination of the electrostatic potential variation across the interface reveals an important charge-separation effect at the interface, which is mostly due to the charge asymmetry between the two cations, Be2+ and Li+. © 2007 Académie des sciences.